2020
DOI: 10.3390/ijms21176393
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Scaffolds in a Vacuum Suction Handle for Intraoperative Stromal Cell Enrichment

Abstract: During total joint replacement, high concentrations of mesenchymal stromal cells (MSCs) are released at the implantation site. They can be found in cell–tissue composites (CTC) that are regularly removed by surgical suction. A surgical vacuum suction handle was filled with bone substitute granules, acting as a filter allowing us to harvest CTC. The purpose of this study was to investigate the osteopromotive potential of CTC trapped in the bone substitute filter material during surgical suction. In the course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Since the ability to adhere onto plastic surfaces is a criterion for mesenchymal stroma cells-the progenitors of osteoblasts-the PMMA filter of the harvesting device may also have a potential to increase the number of MSCs, and thus, promote osteoblast differentiation. As published previously, the cells isolated from SSRT have shown great osteopromotion in vitro [5,53]. This hypothesis is also supported by Groven et al who used the same tissue collector device (BoneFlo ® ) and showed exclusively expressed osteogenic miRNAs as well as overall enhanced osteogenic marker gene expression in SSRT [54].…”
Section: Discussionsupporting
confidence: 68%
“…Since the ability to adhere onto plastic surfaces is a criterion for mesenchymal stroma cells-the progenitors of osteoblasts-the PMMA filter of the harvesting device may also have a potential to increase the number of MSCs, and thus, promote osteoblast differentiation. As published previously, the cells isolated from SSRT have shown great osteopromotion in vitro [5,53]. This hypothesis is also supported by Groven et al who used the same tissue collector device (BoneFlo ® ) and showed exclusively expressed osteogenic miRNAs as well as overall enhanced osteogenic marker gene expression in SSRT [54].…”
Section: Discussionsupporting
confidence: 68%
“…Henze et al (2019) demonstrated that the surgical suction filter can accumulate MSCs during joint replacement surgery [ 72 ]. In the study by Busch et al (2020) porous bone substitute material was placed in the suction device, and the accumulation of mononuclear cells (MNCs), including MSCs, epidermal growth factor, platelet-derived growth factor, and other cytokines in bone substitute material was confirmed [ 73 ].…”
Section: Methods Of Intraoperative Cell Isolationmentioning
confidence: 99%
“…The cytochemical staining demonstrated high osteogenity of the cell-tissue composite (CTC). In total, 104 human cytokines, chemokines, growth factors, hormones and other soluble proteins were detected in the cell tissue composite from the surgical vacuum filter [ 102 ].…”
Section: Surgical-site Surface Coatingmentioning
confidence: 99%